2015
DOI: 10.1021/acs.orglett.5b01066
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Asymmetric Vinylogous Allylic–Allylic Alkylation of Morita–Baylis–Hillman Carbonates with Olefinic Azlactones: Facile Access to Chiral Multifunctional α-Amino Acid Derivatives

Abstract: Vinylogous reactivity of olefinic azlactones was realized through the development of a chiral amine-catalyzed highly stereoselective allylic-allylic alkylation with Morita-Baylis-Hillman carbonates. The Lewis base activation of electrophile and Brønsted base activation of nucleophile were efficiently combined, giving access to multifunctional acyclic α-amino acid derivatives in a highly stereocontrolled manner. The synthetic utility of these versatile synthons was further demonstrated by the facile synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…By following these promising results, we further investigated the reaction with 2.5 and 10 mol% catalyst loading, respectively, but no improvements were obtained ( Table 1, entries 22 and 23). [11] Under these optimum reaction conditions, the CF 3 -containing 3,2'-pyrrolidinyl spirooxindole 4 aa was obtained in 93% yield with > 20:1 dr and 96% ee (Scheme 1). After the evaluation of the above reaction conditions, we found that the desired 3,2'-pyrrolidinyl dispirooxindole 3 aa was instable and unavailable after further purification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By following these promising results, we further investigated the reaction with 2.5 and 10 mol% catalyst loading, respectively, but no improvements were obtained ( Table 1, entries 22 and 23). [11] Under these optimum reaction conditions, the CF 3 -containing 3,2'-pyrrolidinyl spirooxindole 4 aa was obtained in 93% yield with > 20:1 dr and 96% ee (Scheme 1). After the evaluation of the above reaction conditions, we found that the desired 3,2'-pyrrolidinyl dispirooxindole 3 aa was instable and unavailable after further purification.…”
Section: Resultsmentioning
confidence: 99%
“…[10] By contrast, the ringopening reaction performed by treating with potassium carbonate in MeOH was unsatisfactory. [11] Under these optimum reaction conditions, the CF 3 -containing 3,2'-pyrrolidinyl spirooxindole 4 aa was obtained in 93% yield with > 20:1 dr and 96% ee (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The research group of Xu 49 further investigated the vinylogous pro-nucleophilic character of methyl-substituted olefinic azlactones and in 2015 published the first example of an organocatalyzed asymmetric vinylogous allylic-allylic alkylation reaction using Morita-Baylis-Hillman (MBH) carbonates as electrophiles (Scheme 31). 32 The model reaction was the alkylation of the azlactone 68 (R 1 = Ph) to the MBH adduct 44 (R 2 = Ph) and 11 nucleophilic catalysts were screened.…”
Section: Direct Proceduresmentioning
confidence: 99%
“…The allylic substitution reactions using some weak nucleophiles, such as alkyl azaarenes, were very limited [22][23][24][25][26]. In 2014, Rios and coworkers developed a synergistic catalyzed allylic alkylation between electron-deficient 2-ethyl benzoxazoles and MBH carbonates by the combination of a Lewis base and a metal salt [22].…”
Section: Introductionmentioning
confidence: 99%